Performance Characterisric Improvement Of An Upscaled Gammatype Stirling Engine By Using Heat Regenerator - Zan, Muhammad Zaeem Mohamad (Universiti Sains Malaysia, 2017)
The rise of concern on green and sustainable power production system has led to a rise of interest among researchers in developing external combustion engines such as Stirling engine. In this study, an up-scaled gamma-typed Stirling engine with the total swept volume of 85cc., volume compression ratio of 1.5 with the use of mesh-wired heat regenerator has been tested for its performance. The heat regenerator is mesh-wired, made of steel wool with the diameter of 3.2cm and height of 1.5cm which is placed inside the working fluid flow passage in between the displacer cylinder and the power piston cylinder. The working fluid used for the engine operation is air, the heat source is Liquefied Petroleum Gas (LPG) and the cooling jacket to stabilize the cold temperature is using water. Based on the experimental results, it shows that at the heat input of 65J, the gamma engine was able to operate in self-pressurized mode at the hot source temperature of 280C and cold temperature of 32C. The overall performance of the engine using heat regenerator has improved over the performance of the engine without heat regenerator. At no load test condition, the brake power from Beale formula has improved by 1%, brake thermal efficiency (BTE) has improved by 0.9% at the higher temperature difference between hot source and cold temperature of 1% as compared to the engine performance without heat regenerator